Effect of Closing Processus Vagınalis in Orchıdopexy to Recurrence and Testicular Atrophy – 15 Years Experience - Kuas, Nilsun; Ates, Ufuk; Ergun, Ergun; Mammadlı, Aysel; Köksaldı, İrem Semiha; Atasoy, Atike; Cakmak, Ahmet Murat (My University, 2025)
Undescended testis is one of the most common pathologies encountered by pediatric surgeons. In traditional orchidopexy operation, patent processus vaginalis (PPV) is dissected from testicular vessels and spermatic cord. In this study, it was aimed to compare the results of undescended testis patients with and without PPV closure in terms of recurrence and atrophy. After the approval of the local ethics committee, patients who were operated for undescended testis between January 2007 and December 2022 were evaluated. Patients were determined in two groups. first group was with PPV ligation (n=171), second group was without PPV ligation (n=1637). Inguinal hernia was not observed after operation in 15 years of follow-up. There were 23 recurrences (%13,4) in group 1 and 48 recurrences (%2,9) in group 2. According to the preoperative evaluation; A decrease in testicular size was detected in 5 patients (2.9%) in Group 1 and 8 patients (0.4%) in Group 2 in the postoperative follow-up. There is no need to ligate the PPV with additional dissection and open the external oblique fascia if it is predicted that the spermatic cord and testicular vessels may come to scrotum without tension in patients who underwent orchiopexy surgery.
Keywords: Undescended Testis; Orchidopexy; Processus Vajinalis